THE MANAGEMENT OF URBAN SPACE BETWEEN THE CONFLICT OF ACTORS AND FILED REALITY, CASE STUDY: KHENCHELA PROVINCE – AN INLAND CITY IN THE EAST OF ALGERIA - Djebnoune Brahim; Guendouz Berrehail; Messaoud Inasse; Rachi Sana (International Journal of Innovative Technologies in Social Science, 2024)
The demographic explosion of Algerian cities by a positive natural balance and population migration movements transforms urban landscapes and leads them to growing environmental pressure. The resulting spatial increase is more or less planned. It does not only characterize large cities or capitals. The so-called medium-sized cities are also affected, if not more, because they rarely have the assets of large cities to exercise planning and control. The growth of these urban centers has several effects: densification of the fabric, change of urban areas preserved or associated with specific functions, and progress towards agricultural or natural areas. Because it leads to increasing needs for housing and services, growth is reflected in the anarchic extension of the urban area on one hand, and in the appearance of unprompted urban houses on the surroundings of cities. Based on the general hypothesis that urban spatial forms can be analysed using available and supposedly reliable divisions, we attempted to analyse some divisions of Khenchela Province. Our analysis focused on identifying the forms that favour the indications (organizations, directions, temporality, etc.) they provide and the constitution of forms of these divisions. The objectives of the delimitation of urbanization zones (sectors, districts, boroughs) aim to ensure the achievement of the spatial planning orientations from which the objectives are significant. Spatial organization must contribute to the quality of life of the inhabitants, including future generations. (Christophe, 1998) The reaction concerning the organization of the different functions (housing, economic activities, shops, leisure facilities, transport infrastructures, etc.) indeed affects everyone’s living environment. It can have considerable consequences in many areas directly related to Khenchela Province inhabitants.